Pertumbuhan dan Produksi Padi Aromatik Tana Toraja dengan Pemberian Cendawan Rhizosfer dan Pupuk Organik Limbah Pertanian - Abri; Amirudin; A. Fathurrahman Hala (Jurnal Galung Tropika, 2025)
Continuous use of chemical fertilizers hurts soil conditions. The soil hardens quickly, is less able to retain water, and quickly becomes acidic, thus reducing plant productivity. Efforts are needed to use organic fertilizers from agricultural waste and biofertilizers from potential rhizosphere fungi. The purpose of this study was to obtain an effective formulation and combination of organic fertilizers from agricultural waste with 2 species of Rhizosphere fungi isolated from Tana Toraja aromatic rice plants, namely Aspergillus sp and Trichoderma sp, on the growth and production of Tana Toraja aromatic rice plants. This study was designed as a two-factor factorial experiment arranged in a Randomized Block Design. The first factor was three levels: Rhisosphere Fungus C0 = Without Fungus Application, C1 = Rhisosphere Fungus 5 g / liter of water. C2 = Rhisosphere Fungus 10 g / liter of water. The second factor was liquid organic fertilizer/compost from agricultural waste at three levels: K0 = No liquid fertilizer, K1 = 500 ml liquid fertilizer/10 liters of water, and K2 = 1000 ml liquid organic fertilizer/10 liters of water. Nine treatment combinations were replicated thrice, each with two plants, resulting in 54 experimental plots. The results showed that applying Trichoderma and Aspergillus fungi at a dose of 10 g/liter had the best effect. Meanwhile, applying liquid organic fertilizer from cocoa shells and straw at 1000 ml/10 liters of water had the best effect. The best combination/interaction effect was found between the application of 10 g/L rhizosphere fungi and 10 g/L liquid fertilizer, and 1000 ml/L liquid organic fertilizer on the observed components of plant height, number of tillers, number of productive tillers, number of grains/panicle, and panicle length.